A rare case of balloon cell nevus of the vulva in an adolescent - Natalie S.H. Tan; Shi Yun Chia; Coni W. Liu; Mark J.A. Koh (Elsevier, 2020)
Balloon cell nevus (BCN) is a rare variant of benign melanocytic nevus. Clinically, BCN appears similar to regular compound melanocytic nevi. Histopathologically, the balloon cells appear as large, round, polygonal cells with small, round, centrally placed basophilic nuclei, and clear, pale or foamy cytoplasm. We report a case of BCN occurring on the vulva of an adolescent and review the literature on this rare variant of melanocytic nevus, including the differential diagnoses of balloon cells. Recognition of a BCN and differentiating it from other pale cell tumors and balloon cell melanoma is important as it impacts on subsequent management options and prognosis.